2017
DOI: 10.21475/ajcs.2017.11.01.pne165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical treatment on physiological quality of seed and control of Meloidogyne javanica in watermelon plants

Abstract: This study aimed to evaluate the efficacy of different concentrations of abamectin, in combination with thiabendazole and thiamethoxam, on seed physiological quality and on the control of Meloidogyne javanica in watermelon plants. To this purpose watermelon seeds of the Crimson Sweet variety were employed in the study. The treatment of the seeds consisted of abamectin (nematicide) at concentrations of 0.075 g (ST 2 ), 0.150 g (ST 3 ), 0.300g (ST 4 ) and 0.600 g (ST 5 ) ai (active ingredients) per 1000 seeds in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“… da Silva et al (2017) decided that maize seed treatments with abamectin significantly improved most root development variables and abamectin had a large positive effect on seedling health. Rodrigues et al (2017) reported that the quality of the seeds of the watermelon is not affected by the concentration of abamectin when used in 0.75 g up to 600 g/ ai (active ingredients) per 1000 seeds. Hnoosh and Aljuaifari (2020) showed that the okra seeds when treated with abamectin ( Streptomyces avermitilis ) were significantly improved compared to non-treated seeds.…”
Section: Discussionmentioning
confidence: 99%
“… da Silva et al (2017) decided that maize seed treatments with abamectin significantly improved most root development variables and abamectin had a large positive effect on seedling health. Rodrigues et al (2017) reported that the quality of the seeds of the watermelon is not affected by the concentration of abamectin when used in 0.75 g up to 600 g/ ai (active ingredients) per 1000 seeds. Hnoosh and Aljuaifari (2020) showed that the okra seeds when treated with abamectin ( Streptomyces avermitilis ) were significantly improved compared to non-treated seeds.…”
Section: Discussionmentioning
confidence: 99%